Spatial Considerations Needed when Balancing Land Conservation and Development - Basil V Iannone III; Tina McIntyre; Alexander J. Reisinger; Eban Z. Bean; Abbey Tyrna; Brooke L. Moffis (EDIS)
Designers, builders, and managers of sustainable urban areas must consider location and proximity of conserved land, built infrastructure, and designed urban ecosystems such as stormwater ponds and ornamental gardens. This publication introduces four key spatial considerations and discusses their implications for conservation of native plants and animals and the biodiversity and ecological benefits provided by urban landscapes. Planners, builders, and managers must recognize and conserve spatial differences in habitat types and understand how the size, shape, and location of conserved lands and urban ecosystems affect plant and animal welfare and movement. The publication lists multiple free tools for visualizing and measuring spatial aspects and stresses that conserved areas and designed ecosystems must be properly managed to reap benefits from good spatial planning. People can use the information to improve the design, construction and management of sustainable urban areas.